Chronic Kidney Disease and Serum Uric Acid Level in Hypertensive and/or Diabetic Patients - Danilo Lemes Naves Gonçalves; Luciana Saraiva da Silva (Publicações Ciência e Vida, 2023)
Introduction: Chronic kidney disease is a worldwide health problem. Uric acid seems to have a relationship with chronic kidney disease, but its role is still controversial. The aim of the present study was to estimate the prevalence of chronic kidney disease in hypertensive and/or diabetic patients in a Basic Family Health Unit and to evaluate the association of uric acid levels with chronic kidney disease. Methods: A cross-sectional study was conducted with 182 adults with arterial hypertension and/or diabetes mellitus followed-up in a Basic Family Health Unit between 2019 and 2020. Demographic, clinical, behavioural and biochemical data were collected through the review of medical records. The exposure of interest was the uric acid and the outcome was chronic kidney disease. For the association of uric acid and chronic kidney disease, univariate and multivariate logistic regression analysis were performed. Results: The prevalence of chronic kidney disease in the sample was 17% (95% CI = 12.1-23.3). After adjustment analysis for age, sex, arterial hypertension, diabetes mellitus, cardiovascular diseases, dyslipidemia, smoking, alcohol consumption, antihypertensive and lipidlowering drugs, there was a positive association (ORa = 1.65 (95%CI = 1.11-2.45), p = 0.013) between uric acid and chronic kidney disease. Conclusion: The increase in uric acid in 1 mg/dL was associated with a 1.6 times higher chance of chronic kidney disease in hypertensive and/or diabetic population.